2002
DOI: 10.1016/s0092-8674(02)00871-1
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Hox Gene Deformed Sculpts Head Morphology via Direct Regulation of the Apoptosis Activator reaper

Abstract: Hox proteins control morphological diversity along the anterior-posterior body axis of animals, but the cellular processes they directly regulate are poorly understood. We show that during early Drosophila development, the Hox protein Deformed (Dfd) maintains the boundary between the maxillary and mandibular head lobes by activating localized apoptosis. Dfd accomplishes this by directly activating the cell death promoting gene reaper (rpr). One other Hox gene, Abdominal-B (Abd-B), also regulates segment bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 57 publications
2
173
1
3
Order By: Relevance
“…Our data show a clear increase in spiracle-associated cell death in A7 of both sexes. It has been reported that posterior embryonic apoptosis is positively regulated by Abd-B directly through activation of the proapoptotic gene reaper (42). If similar Abd-B-mediated regulation of apoptosis occurs during pupal development, there must be additional regional controls that restrict these events to those cells surrounding the developing spiracles.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show a clear increase in spiracle-associated cell death in A7 of both sexes. It has been reported that posterior embryonic apoptosis is positively regulated by Abd-B directly through activation of the proapoptotic gene reaper (42). If similar Abd-B-mediated regulation of apoptosis occurs during pupal development, there must be additional regional controls that restrict these events to those cells surrounding the developing spiracles.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Although these results could be interpreted to indicate that IAPs do not play a major role for caspase regulation in mammals, a more likely alternative is that their physiological role is masked by functional redundancy. If relatively short-lived organisms such as fruit flies protect themselves against unwanted death using multiple caspase inhibitors (see below; Figure 1), 6,[8][9][10][11][12][13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] it would come as a great surprise if mammals would employ fewer safeguards to control caspase activity.…”
Section: Brakes On Death: Caspase Inhibition By Inhibitor Of Apoptosimentioning
confidence: 99%
“…38 The reaper gene, and to some extent grim, hid and sickle, are transcriptionally activated in response to many different proapoptotic signals, including steroid hormones, a variety of developmental signals, radiation and various forms of cellular stress or injury. [24][25][26]36,[39][40][41] These genes share a very large, complex regulatory region containing numerous enhancer (and silencer) elements that are the target for many different transcriptional regulators. Therefore, one major mechanism by which different signaling pathways converge in Drosophila is through transcriptional activation of reaper, hid and grim.…”
Section: Relieving the Brakes: Induction Of Apoptosis By Reaper-familmentioning
confidence: 99%
“…It is still not fully understood how developmental pathways integrate both differentiation and apoptosis in tissues. The identification of developmental factors, such as Deformed, Abdominal B, which regulate RHG gene transcription [17], was a step towards the identification of rpr transcriptional regulators but a thorough analysis of findings is needed to fully understand the transcriptional regulation of RHG genes. Recently, Zhou and colleagues showed that epigenetic regulations play an active part in the coordinated expression of rpr and hid during apoptosis in embryos, suggesting that a complete understanding of RHG regulation may lie in alternative approaches [18].…”
Section: Apoptosis During Embryogenesismentioning
confidence: 99%